Patterns of Communication and Mother-in-Law Support in Supporting Exclusive Breastfeeding Practices and Infant Nutrition - Hidayah, Seventina Nurul; Fatimah, Okta Zenita Siti (International Conference on Sustainable Health Promotion, 2023)
This study aims to investigate the patterns of communication and support provided by parents-in-law to mothers in supporting exclusive breastfeeding practices and fulfilling infant nutrition. This research method involves a qualitative study with data collection through in-depth interviews and content analysis. The location of the research was carried out in the District of South Tegal. Purposive sampling technique was used to select informants. The main informants in this study were mothers who practiced exclusive breastfeeding and lived with their in-laws. while the triangulation informants were the in-laws of the main informants and each of them was 7 people. In the context of the importance of exclusive breastfeeding for the health and development of babies, the role of in-laws as part of the family environment has significant potential in shaping the success of this practice. Research results reveal a variety of communication patterns, ranging from understanding and positive support to less supportive attitudes. Emotional, informational and practical support also plays a role in influencing the success of exclusive breastfeeding practices. These findings provide insight into the important role of in-laws in supporting mothers in breastfeeding and infant nutrition practices, and highlight the need for a holistic educational approach to ensure consistent support for mothers on this journey.